A Topographic Comparison of OCT Minimum Rim Width (BMO-MRW) and Circumpapillary Retinal Nerve Fiber Layer (cRNFL) Thickness Measures in Eyes With or Suspected Glaucoma. Issue 8 (August 2020) - La Bruna, Sol; Tsamis, Emmanouil; Zemborain, Zane Z.; Wu, Zhichao; De Moraes, Carlos Gustavo; Ritch, Robert; Hood, Donald C.
Abstract : Précis: Bruch's membrane opening-minimum rim width (BMO-MRW) and circumpapillary retinal nerve fiber layer (cRNFL) thickness measures may be improved by comparing probability levels and accounting for blood vessel locations. Purpose: To understand the differences between 2 optical coherence tomography measures of glaucomatous damage: the BMO-MRW and cRNFL thickness. Materials and Methods: Optical coherence tomography circle scans were obtained for an early glaucoma group (EG) of 88 eyes (88 patients) with 24-2 mean deviation better than –6.0 dB, and a broader group (BG) of 188 eyes (110 patients) with 24-2 mean deviation from −0.15 to −27.0 dB. On the basis of a commercial report, the cRNFL and BMO-MRW of each hemidisc was classified as abnormal if either of the 2 superior (inferior) sectors, temporal superior and nasal superior (temporal inferior and nasal inferior), was yellow or red ( P <5%); and as normal if both were green ( P ≥5%). In addition, a post hoc analysis identified the reasons for disagreements on the basis of the presence (or absence) of glaucomatous damage at a hemidisc level (consensus of 4 experts). Results: The BMO-MRW and cRNFL measures agreed in 81.9% (broader group) and 73.9% (EG) of the hemidiscs. In both groups, an abnormal-BMO-MRW/normal-cRNFL disagreement was as common as a normal-BMO-MRW/abnormal-cRNFL. Of the 46 EG hemidisc disagreements, the number of "mistakes" for BMO-MRW (28) was nonsignificantly higher than for cRNFL (18) ( P =0.15). Primary causes for disagreement were as follows: borderline significance level, a local defect, and aberrant blood vessel location. Conclusions: Although BMO-MRW and cRNFL measures agreed in the majority of hemidiscs, they still disagreed in over 25% of the EG hemidiscs. These measures may be improved by comparing actual probability levels and accounting for blood vessel locations. However, both can miss information available on retinal ganglion cell/retinal nerve fiber layer probability maps.